A cohort comparative study between laparoscopic and open appendectomy in pregnant women - Bellapu, Srujan Kumar (International Surgery Journal, 2019)
Background: Despite the initial absolute contraindication of laparoscopic surgery during pregnancy, in the last decade, laparoscopic appendectomy (LA) has been performed in pregnant women but to compare the outcomes of LA compared with open appendectomy (OA). The objective of the study was to evaluate the safety and efficacy of LA compared with OA in pregnant women. Methods: A cohort study was conducted among pregnant women with a diagnosis of acute appendicitis who were undergoing LA or OA between June 2013 to July 2014. Pre-operative data and post-operative complication were monitored. Epi-info 7 was used for analysis. Results: Sixty patients (20 LA and 40 OA) enrolled in our study. There were no significant differences in duration of surgery, postoperative complication rate and obstetric outcomes, including incidence of preterm labour, delivery type. The mean time to normal bowel movement in the LA group was significantly shorter than that in the OA group. Also, the mean time to adequate oral intake in the LA group was earlier than in the OA group (2.1±0.4 d v. 4.1±1.8 d, p=0.02). Duration of hospital stay in the LA group was 4.1±2.6 days, and that of the OA group was 6.6±3.2 days (p=0.04). Conclusions: Laparoscopic appendectomy is a clinically safe and current procedure in all trimesters of pregnancy and should be well-thought-out as a standard treatment alternative to OA.